Space Debris Low Earth Orbit (LEO) - Ahmed Mohamed, Fatima; Mohamad Ali, Noor Azian (International Journal of Science and Research, 2015)
Humans have created a lot of garbage on earth surface to which we can see, but up in the atmosphere, unbelievably the amount of junk human have created in space is equally colossal. The main topic of this paper is to discuss space debris particularly in LEO orbit. The discussion starts with the satellites basic characteristics and move on to debris history and development. Some previous studies and researches done with regard to the debris conditions are discussed. Statistics on the debris growth and its impact to the active satellite and space craft’s located in LEO orbit are presented. Finally, the paper mentioned on space debris removal system. The main question this paper tries to address is why LEO orbit has the most number of debris and the impact of the growth to the future.